2010
DOI: 10.1074/jbc.m109.079673
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Composition Regulates the Orientation of Transmembrane Helices in HorA, an ABC Multidrug Transporter

Abstract: ATP-binding cassette (ABC) transporters constitute a large class of molecular pumps whose central role in chemotherapy resistance has highlighted their clinical relevance. We investigated whether the lipid composition of the membrane affects the function and structure of HorA, a bacterial ABC multidrug transporter. When the transporter was reconstituted in a bilayer where phosphatidylethanolamine (PE), the main lipid of the bacterial membrane, was replaced with phosphatidylcholine (PC), ATP hydrolysis and subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
36
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 29 publications
6
36
0
Order By: Relevance
“…These are all membrane transport proteins with high degrees of conformational flexibility. In addition, the following transporters from other sources show a requirement for PE after reconstitution into liposomes in order to display uphill transport, which is not satisfied by PC: the multidrug transporter (LmrP) of L. lactis (22,23), the leucine permease of P. aeruginosa (24), the branched chain amino acid transporter of S. cremoris (25), and the ABC transporter HorA from L. lactis (26). Because in all cases the dioleoyl form of PC was used, the lipid dependence for supporting uphill transport needs to be reinvestigated in the above cases using a variety of PC species in vitro and expression in cells containing PC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These are all membrane transport proteins with high degrees of conformational flexibility. In addition, the following transporters from other sources show a requirement for PE after reconstitution into liposomes in order to display uphill transport, which is not satisfied by PC: the multidrug transporter (LmrP) of L. lactis (22,23), the leucine permease of P. aeruginosa (24), the branched chain amino acid transporter of S. cremoris (25), and the ABC transporter HorA from L. lactis (26). Because in all cases the dioleoyl form of PC was used, the lipid dependence for supporting uphill transport needs to be reinvestigated in the above cases using a variety of PC species in vitro and expression in cells containing PC.…”
Section: Discussionmentioning
confidence: 99%
“…Because phosphatidylserine supports uphill transport and progressive methylation of the amine of PE resulted in a parallel decrease in the level of uphill transport observed in vitro, it was suggested that an ionizable amine was required to support uphill transport (13). PC also did not substitute for PE in proteoliposome studies of proline transport by PutP from E. coli (21), multidrug transport by LmrP from Lactococcus lactis (22,23), leucine transport by the leucine permease from Pseudomonas aeruginosa (24), branched chain amino acid transport by the transporter from Streptococcus cremoris (25), and the ABC transporter HorA from L. lactis (26). The failure of PC to substitute for PE in the case of LacY as well as several other secondary transporters has led to the general conclusion that an ionizable lipid amine may be either involved directly in the transport mechanism or required for proper assembly.…”
mentioning
confidence: 99%
“…An ionizable amine or hydrogen bond donor capacity is also required for uphill transport because methylation of the amine of PE progressively reduces activity (10,11). PE but not diC 18∶1 PC or eukaryotic-derived PC also supports uphill transport by the multidrug transporter (LmrP) of Lactococcus lactis (12,13), the leucine permease of Pseudomonas aeruginosa (14), the branched chain amino acid transporter of Streptococcus cremoris (15), the ABC transporter HorA from Lactococcus lactis (16), and the Ca 2þ ATPase of the sarcoplasmic reticulum (17).…”
mentioning
confidence: 99%
“…The bacterial ABC multidrug transporter HorA of Lactobacillus brevis required PE for ATPcoupled substrate extrusion from liposomes (Gustot et al, 2010). When PE was replaced by PC, transport activity was abolished even though it hydrolyzed ATP at more than twice the rate than in PE.…”
Section: Horamentioning
confidence: 95%